Keanekaragaman Jenis Mangrove Di Kawasan Hutan Mangrove Di Desa Mirring Polewali Mandar - Nirwana; Bulan, Rita; Rusmidin (Pangale Journal of Forestry and Environment, 2024)
This study aims to determine the types of mangroves that grow in the Mirring Village Mangrove Forest Area Polewali Mandar Regency and Know the diversity of mangrove plant species that thrive in Mirring Village Polewali Mandar Regency. The population in this study are mangroves that grow in the Mirring Village mangrove forest area. The sample in this study was all types of mangroves in the Mirring Village mangrove forest area. This research uses quantitative methods. Data collection uses the striped path method, which combines the transect method with the plot method. Data analysis was done by calculating the composition of vegetation types and ecological indices of mangrove forests The results showed that the types of mangroves found in Tappina Hamlet Mirring Village there are 9 types namely Sonneratia alba, Rizhopora Stylosa, Xylocarpus muloccesnsis, Bruguiera gymnorrhiza, Rhizopora mucronata, Rhizophora apiculata, Bruguiera Parviflora, dolichandrone spathacea, excoecaria agallocha. Mangrove species diversity level showed moderate species diversity including trees 1.41, saplings 1.58 and seedlings 1.59. Keywords: Mangrove, Diversity, Polewali.